The genus Holopothrips Hood, 1914 in Guadeloupe with descriptions of two new species (Thysanoptera, Phlaeothripidae) - Michel, Bruno; Etienne, Jean (Zootaxa, 2020)
After the revision of the genus Holopothrips provided by Lindner et al. (2018), the specimens of Holopothrips kept in the CIRAD/CBGP collection collected in Guadeloupe were re-examined. Two species previously identified as Holopothrips tenuis and Holopothrips sp. are described here as H. brevisetus sp. n. and H. guadeloupensis sp. n. Holopothrips ananasi is here removed from the list of species reported to Guadeloupe after re-examination of labelled specimens. Information on all the species of Holopothrips found in Guadeloupe, and an identification key to the species of Holopothrips recorded from the Caribbean are provided.